'What will it take': addressing alcohol use among people living with HIV in South Africa. (October 2019) - Sorsdahl, K; Morojele, NK; Parry, CD; Kekwaletswe, CT; Kitleli, N; Malan, M; Shuper, PA; Myers, B
Given that hazardous and harmful alcohol use has been identified as a significant barrier to adherence to antiretroviral therapy (ART) in South Africa, alcohol reduction interventions delivered within HIV treatment services are being investigated. Prior to designing and implementing an alcohol-focused screening and brief intervention (SBI), we explored patients' perceptions of alcohol as a barrier to HIV treatment, the acceptability of providing SBIs for alcohol use within the context of HIV services and identifying potential barriers to patient uptake of this SBI. Four focus groups were conducted with 23 participants recruited from three HIV treatment sites in Tshwane, South Africa. Specific themes that emerged included: (1) barriers to ART adherence, (2) available services to address problematic alcohol use and (3) barriers and facilitators to delivering a brief intervention to address alcohol use within HIV care. Although all participants in the present study unanimously agreed that there was a great need for SBIs to address alcohol use among people living with HIV and AIDS, our study identified several areas that should be considered prior to implementing such a programme.